COMPARISON OF OUTCOMES BETWEEN LINEAR VERSUS TRIANGULAR FLAP REPAIR TECHNIQUES AT VERMILION IN UNILATERAL CLEFT LIP REPAIR - Cheema, Saeed Ashraf; Asim, Muhammad; Ahmad, Awais (Journal of Ayub Medical College Abbottabad, 2012)
Background: Surgery for unilateral cleft lip repair has evolved over centuries. Many studies give detailed inside to this process of evolution of various techniques and their modifications. Objectives were to compare linear repair of Millard rotation advancement technique and triangular flap technique of Nordhoff, at vermilion in unilateral cleft lip repair. Methods: This cross-sectional analytical study was conducted at Departments of Plastic Surgery, Services Institute of Medical Sciences, and WAPDA Teaching Hospital Complex, Lahore form Jan 2004 to Dec 2011. Patients presenting with unilateral cleft lip deformity were included in the study. In the early part of the study (2004-2008), only Millard linear repair at vermilion was the routine practice. Last consecutive 40 cases repaired with this technique during this period were selected for the study. From 2009 to 2011 the unilateral cases were operated with Nordhoff triangular flap repair. A group of 40 consecutive cases repaired with this technique was also selected for the study. In both groups, the postoperative period exceeded one year. Results were compared for the presence of notch on repaired vermilion area. Results: Notch was absent in 29 cases (72%) treated with Millard Technique whereas Noordhoff Technique Group showed a higher number of 34 cases (85%). On other extreme, a notch of more than 1 mm was evident in two cases (5%) of Millard technique only and Noordhoff technique did not show this wide notch at vermilion. Similarly, two subgroups of 0.5 mm notch and 0.5-1 mm notch had a slightly higher number of cases in group dealt with Millard technique (5 and 4 cases respectively) as compared to cases dealt by Noordhoff technique (3 cases in each subgroup). Conclusion: Nordhoff triangular flap repair at vermilion reduces the chances of notching to minimum due to break in the linear repair in vermilion and also helps in reconstructing a symmetrical vermilion by bringing in the vermilion from lateral to medial segment. Keywords: Flap repair, cleft lip, congenital